2013
DOI: 10.1021/jp3112183
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Titanium(IV) Dioxide with Small Silver Nanoparticles: Application in Photocatalysis

Abstract: The surface of commercial TiO2 compounds (P25 and ST01) has been modified with Ag nanoparticles induced by radiolysis. On P25, the Ag nanoclusters are very small (1–2 nm) and homogeneous in size while on ST01, two populations of nanoparticles are obtained, small nanoparticles (1–2 nm) and larger ones (mean diameter 7 to 12 nm depending on the silver loading). The photocatalytic properties of Ag-modified TiO2 have been studied for phenol photodegradation in aqueous suspensions under UV and visible light. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 69 publications
8
117
4
Order By: Relevance
“…6 showed that the catalyst exhibited their Ag3d level two peaks (at around 368 and 374 eV), which indicated for the Ag 3d5/2 and 3d3/2. The binding energy of peak Ag 3d5/2 maximum at 368.1 eV was close to the value reported for metallic Ag(0) [12].…”
Section: Fig 4:tem Images Of Tio2 (P25) (A) and Ag 30-ni15/tio2 (Bsupporting
confidence: 85%
See 1 more Smart Citation
“…6 showed that the catalyst exhibited their Ag3d level two peaks (at around 368 and 374 eV), which indicated for the Ag 3d5/2 and 3d3/2. The binding energy of peak Ag 3d5/2 maximum at 368.1 eV was close to the value reported for metallic Ag(0) [12].…”
Section: Fig 4:tem Images Of Tio2 (P25) (A) and Ag 30-ni15/tio2 (Bsupporting
confidence: 85%
“…Silver and nickel doped TiO2 by sol-gel method applied against bacteria under UV and visible light irradiations [7]. Various methodsfor the synthesis of modified TiO2photocatalyst included precipitation [8] , hydrothermal, solvothermal [9], chemical vapour deposition [10], and electrospinning [11] , radiolysis [12]. Among several methods for modified nanopowder TiO2, radiolysis method using-irradiation is advantageous because the experiment can be carried out at very mild conditions, ambient pressure and room temperature with high reproducibility and it is the unique method [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…They could be reused, and handled more easily and economically if impregnated on substrates. Therefore, many researchers have focused on modifying TiO 2 with Ag by synthesis Ag/TiO 2 heterostructures [8][9][10][11][12][13][14]23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Although the synthesis of Ag/TiO 2 heterostructures was intensively reported in large quantities [8][9][10][11][12][13][14]23,24], there are few reports about Ag/TiO 2 composite thin films with amounts of Ag > 18 mol%, prepared by chemical methods such as sol-gel, so far in the literatures. It is well reported that incorporating larger amount of Ag particles was limited by the sol-gel dip-coating method of up to 18 mol% due to Ag particles coalescing with each other into huge particles during sintering [25].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, by contrast, MTG has a heightened photocatalytic activity to a certain extent and MTGA presents the prominently highest photocatalytic activity, whereby when the illumination time is 120 min, the degradation rate of MTGA-8 reaches 93% and the apparent reaction rate constant of the ternary material in Figure 8b is 0.017 min -1 , which is almost 3.4 times the degradation rate of MTG, when silver content is added up to 10%, the degradation rate does not rise rather reduced for that too much deposition of Ag nanoparticles themselves can become the recombination center that suppressing the carrier separation. [43] The stability of MTGA-8 is exhibited in Figure 9, after three cycle times, the degradation rate reduce to 91.2%. The result indicates MTGA exhibits an excellent photocatalytic capacity and the highest stability.…”
Section: Introductionmentioning
confidence: 98%